EPIDEMIOLOGY OF ROAD TRAFFIC ACCIDENTS IN GHANA - Hesse, Christian A.; Ofosu, John B. (European Scientific Journal, ESJ, 2014)
In this paper, we shall discuss the morbidity and mortality of road traffic accidents (RTAs) and other epidemiological variables of RTAs in Ghana between 1991 and 2011. The study will show that more than two thousand people died annually during the period. The average incidence of the morbidity and mortality patterns from RTAs in the period were 61.9 and 7.6 per 100 000 population, respectively. The morbidity pattern was similar throughout the same period with a mean of 1.2 per accident and a variance of 0.0093. Mortality rate per 100 accidents between 1991 and 2011, increased from 11.0 to 20.2, during this period, representing an increase of 83.6%. Although the number of accidents increased during the period 1991 to 2011, the number of fatal and injurious accidents per 100 road traffic accidents remained almost constant, with an average of 14.8 and 62.0, respectively. The highest fatalities during the period 1991 to 2011 were in the 26 – 35 year old age group. Road traffic accidents are responsible for a far higher rate of death among men, by an approximate ratio of 3:1. The highest incidence of road traffic accidents was in the month of November, followed by the month of December. Saturday stood out as the day during which most road traffic accidents occurred. Pedestrians were more likely to be injured or killed in a road traffic accident, than all other road users.